Self-efficacy, empowerment and power of middle nurse managers in Cyprus: A correlational study - Leontiou, Ioannis; Merkouris, Anastasios; Papastavrou, Evridiki; Middleton, Nicos (My University, 2021)
Aim To investigate the perceived self-efficacy, structural empowerment and power of middle nurse managers before the implementation of a major reform of public hospitals in Cyprus. Background Nurse managers’ self-efficacy is important as it makes a difference in nurses’ motivation and the way they feel, think and behave. Empowerment promotes workers' engagement at work, leading to positive performance outcomes. Methods This is a descriptive correlational study with a sample of 175 nurse managers. It was conducted during March–April 2019. Results The results showed that nurse managers perceived relatively high scores of self-efficacy, moderate levels of empowerment and moderate levels of both formal and informal power. Access to resources has been recorded as low. Statistically significant correlations have been found between self-efficacy, age and work experience. Nurse managers with a bachelor's degree had a higher informal power than those with a master's degree. Conclusions The present study provides recommendations for maintaining and enhancing the self-efficacy, empowerment and power of nurse managers in the evolving conditions of health care reforms. Implications for Nursing Management Nurse managers need to improve their access to empowerment structures and be involved in policy decision-making, future planning, organisation and control, aiming for the improvement of services and care that they provide.
Keywords: Empowerment; Nurse managers; Power; Self-efficacy